Dampak Pemasaran Holistik terhadap Kinerja Institusi Pendidikan: Sebuah Tinjauan Pustaka - Widyastuti, Yulinda Dika (Journal of Education Management Research, 2024)
The holistic marketing approach has been widely recognized as a comprehensive strategy that integrates various marketing elements to create synergy within an organization. This literature review aims to examine the impact of holistic marketing strategies on the performance of educational institutions. The review explores various aspects of holistic marketing, including internal and external marketing, relationship marketing, and integrated marketing communications, and how these elements influence educational leadership, resource management, and organizational performance. The study uses a qualitative approach to analyze existing literature from multiple sources, focusing on the application of holistic marketing in the education sector. The findings suggest that a well-implemented holistic marketing strategy can enhance institutional performance by improving resource management, fostering strong relationships with stakeholders, and strengthening leadership in educational organizations. The review concludes by highlighting the importance of adopting holistic marketing strategies for educational institutions to achieve sustainable success in a competitive environment.